Construction of trisubstituted chromone skeletons carrying electron-withdrawing groups via PhIO-mediated dehydrogenation and its application to the synthesis of frutinone A - Li, Qiao; Zhuang, Chen; Wang, Donghua; Zhang, Wei; Jia, Rongxuan; Sun, Fengxia; Zhang, Yilin; Du, Yunfei (Beilstein Journal of Organic Chemistry, 2019)
The construction of the biologically interesting chromone skeleton was realized by PhIO-mediated dehydrogenation of chromanones under mild conditions. Interestingly, this method also found application in the synthesis of the naturally occurring frutinone A.
Keywords: chromanone; chromone; dehydrogenation; frutinone A; PhIO